Diagnostic and Therapeutic Patents and Patent Applications on Biomarkers for Acute Kidney Injury - Liangos, Orfeas (Recent Patents on Biomarkers, 2012)
Acute kidney injury (AKI), a syndrome that is defined by a sudden and substantial decrease in kidney function, can be caused by a variety of mechanisms including circulatory collapse, ischemia-reperfusion injury, systemic inflammatory response, endogenous or exogenous toxicants or urinary obstruction. The causal and temporal sequence of kidney injury leading to reduced function and in turn causing an increment in serum creatinine, however, hinders a timely detection of this syndrome and may therefore also delay its early and effective treatment. In recent years, an increasing number of promising biomarker candidates were described and patented to help in the detection, prognostic stratification and treatment of AKI. The discovery and evaluation of novel biomarkers for AKI holds the promise to improve early detection and allow for the development of effective treatments for this condition. This narrative review summarizes recent developments in AKI biomarker patenting with a focus on both diagnosis and treatment-oriented patents and patent applications. In addition, alternative methods for early detection of AKI, particularly patents and patent applications on continuous urine output- and glomerular filtration rate monitoring, are presented and discussed in comparison. Finally, important potential limitations for the application of biomarkers for AKI as well as alternative techniques for the measurement of kidney function are discussed.
Keywords: clinical research